PEMANFAATAN MEDIA SOSIAL INSTAGRAM DALAM MEMPROMOSIKAN PARIWISATA PULAU BANGKA (Studi Kasus Pada Akun Instagram @tic_bangka) - Felia Agni Lestari (2024)
Bangka Island is a tourism destination that is rich in natural beauty, especially marine tourism. However, as a result of the pandemic, tourist visits to Bangka Island have decreased. Social restrictions implemented by the government are increasingly having an impact on the tourism sector. This encourages local governments to make recovery efforts through social media. Instagram is considered an effective means for promoting tourism. This research aims to find out how the social media Instagram @tic_bangka is used in promoting Bangka Island tourism. The research method used is descriptive qualitative using a case study approach. Data was collected through interviews, observation and documentation. This research uses a purposive sampling technique to determine informants. The six informants involved in this research included the local government, @tic_bangka account admin, travelers, the community, Bangka tourism ambassadors, and account followers. The object of this research is the Instagram account @tic_bangka and the interactive model analysis of Miles and Huberman used in analyzing research data. The data validity technique uses data source triangulation. The research results show that the Instagram account @tic_bangka has succeeded in utilizing several features such as reels, IG Stories, feeds, and others to create interesting tourism content. The content not only serves as a promotional visual tool, but also as a primary source of information for potential tourists. Instagram @tic_bangka has also been proven to have other roles besides its important role as a promotional medium, namely helping to increase the number of visitors, providing information on tourist destinations, publishing tourism event calendars, as well as being a video viewing platform and presenting detailed tourism content. However, several obstacles are faced, such as budget limitations in content production, writing errors that require further evaluation and minimal content being shared due to a lack of human resources in project involvement.